2002
DOI: 10.1103/physrevb.65.165311
|View full text |Cite
|
Sign up to set email alerts
|

Hopping conduction in GaAs layers grown by molecular-beam epitaxy at low temperatures

Abstract: The electrical conductivity of GaAs layers grown by molecular-beam epitaxy at low temperatures was studied by using the van der Pauw method. The electrical conductivity of thick GaAs layers grown at temperatures above 200°C changes with the concentration of antisite As atoms following the nearest-neighbor hopping model. From the dependence of the conductivity on the average spacing of antisite As atoms, the Bohr radius of the donor wave function in the hydrogen like model was estimated to be between 2.8 and 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
(18 reference statements)
2
12
0
Order By: Relevance
“…Another approach concerning hopping conduction in GaAs layers was presented by Shimogishi et al [34], Albuquerqe et al [35] and Rubinger et al [36]. They reckon that GaAs layer grown by molecular-beam epitaxy at low temperatures contains a high concentration of excess As as a form of point defects [37].…”
Section: Discussionmentioning
confidence: 97%
“…Another approach concerning hopping conduction in GaAs layers was presented by Shimogishi et al [34], Albuquerqe et al [35] and Rubinger et al [36]. They reckon that GaAs layer grown by molecular-beam epitaxy at low temperatures contains a high concentration of excess As as a form of point defects [37].…”
Section: Discussionmentioning
confidence: 97%
“…The condition used for the growth of the ultrathin LT-GaAs layer is known to give rise to a high concentration of antisite As atoms without forming the extended defects of our earlier study. 5 The concentration of antisite As atoms in ultrathin LT-GaAs layers grown under similar conditions was found to range from 2ϫ10 20 to 4ϫ10 20 cm Ϫ3 by x-ray-diffraction analyses. 5,14 An As flux for growth of the GaAs cap layer is 6.2ϫ10 Ϫ6 Torr, which is known to give rise to a nearly stoichiometric LT-GaAs layer with the aforementioned growth rate.…”
Section: Methodsmentioning
confidence: 96%
“…4 A lower concentration of carriers is also expected to lead to stronger localization because of reduced screening of random potentials. During the course of investigation of electrical conduction in ultrathin GaAs layers grown at low temperatures ͑LT-GaAs͒ by molecular-beam epitaxy ͑MBE͒, 5 we have found strong localization of carriers in Be ␦-doped wells, considered to result from the above three methods.…”
Section: Introductionmentioning
confidence: 98%
“…In LT-MBE GaAs the gallium vacancies V Ga play the major role as acceptors [10]. This defect is known as a deep triple acceptor [7]. Regarding the V Ga concentrations, Gebauer et al [10] found densities of 10 18 cm −3 and 10 17 cm −3 for T G of 200 o C and 300 o C, respectively.…”
Section: Discussionmentioning
confidence: 99%